PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN DI RESTORAN OBONK STEAK AND RIBS : Survei Pada Restoran Obonk Steak And Ribs Cabang Dipatiukur Bandung - Nyimas Emilia, - (2009)
This study aims to determine: the influence of product quality to customer loyalty restaurant steak and ribs obonk Dipatiukur bandung branch and the influence of service quality on customer loyalty restaurant steak and ribs Obonk Dipatiukur branch of Bandung. The independent variable in this study is the quality of the product (X) and the quality of service (X), while the bound variable in this study is customer loyalty (Y). Research methods used in this research is analytical descriptive method with systematic nonrandom sampling technique that is incidental technique. Sample in this study were 100 people in the restaurant steaks and ribs Obonk. The data analysis in this research is regresi double linier. Research results show that the influence of product quality and service quality jointly on customer loyalty is 8.7% while the rest influenced by other factors. The variable quality of products has the greatest influence compared with the variable quality of service, ie for 46.6% while for the variable quality of service for 36.5% The Management of obonk steak and ribs should be able to adapt, improve and continue to renew the level of product quality of reliability dimension, precisely on the possibility indicators of food and beverages those not served well, then the aesthetic dimension of taste-level indicators of food and beverages that could be inspire and also on the performance dimension of freshness indicators of food and beverages. Otherwise the service quality of restaurant steaks and ribs Obonk are expected to continue to be developed on the dimensions of the physical facility, precisely the ease in finding indicators Restaurant steak and ribs Obonk and also on employee's performance indicators of restaurant steak and ribs Obonk.